Review Study on Stabilized Fly Ash Type C as Pavement Material in Pavement Design - Mahmood, Muhammad Amirul Hakim; A. Khalifa, Nasradeen (Recent Trends in Civil Engineering and Built Environment, 2022)
Fly ash, also known as the residues of fine particles that formed with flue gases is a by-product which can be found at thermal power stations. There are two types of fly ash, which are Type C and Type F. This material can be used in construction of buildings or infrastructures as a new alternative to reduce material costs if the material can achieve an adequate performance as a construction material. With the use of fly ash, Portland cement usage can be reduced hence it promotes sustainable development. The aim of this study are to evaluate the properties and suitability of stabilized fly ash Type C as pavement base material and to propose a suitable design of pavement for Jalan Kluang in Johor with the use of stabilized fly ash Type C. Several past researches are reviewed to study the chemical and physical properties of stabilized fly ash Type C and they conducted various tests such as Unconfined Compression test, California Bearing Ratio (CBR) test, Resilient Modulus test, and non-destructive deflection test with falling weight deflectometer (FWD) on the specimens containing stabilized fly ash Type C material. It was found that fly ash Type C with almost optimum water content (less than 5%) significantly increase the compressive strength, CBR value and resilient modulus of stabilized soil when mixed. In addition, 8% of fly ash Type C are applied by weight plus optimum water content of 5% for maximum strength to a recycled asphalt base course with cold in-place recycling (CIR) method and the results showed that the structural coefficient of fly ash is slightly higher compared to traditional crushed aggregate base course. These researches showed that fly ash-stabilized material (FASM) significantly improve bearing resistance and stiffness of a pavement.